AN INVENTORY OF DIVERSITY OF BUTTERFLY SPECIES IN LUCKNOW REGION OF NORTHERN INDIAN PLAIN - SRIVASTAVA, RAJESH KUMAR; RIZVI, SABREEN; MISHRA, SHIVANGI; KANAUJIA, AMITA; CHAND, SHEKHAR; RATN, ARUN (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Butterflies are more elegant and appealing than most insects, they are included in the order Lepidoptera. They are varied in shape, size and colour. They are found everywhere throughout the world apart from the poles. The present study aims to provide a baseline for the analysis of population status of butterfly species and their dispersion in Lucknow region. The butterfly individuals were collected randomly for twelve consecutive months, August 2021 to July 2022. The butterfly data was collected by using the photographic evidences, capture and release method as well as by visual observations. The butterfly diversity was determined to quantify the values of Shannon diversity index (H) and Simpson diversity index (D). Notably, 40 species of butterfly of 5 families and number of individuals of each species were monthly recorded during the entire period. Overall, this site showed higher diversity of butterfly species. In this region, the Shannon-Weiner diversity index (H) and Simpson diversity index (D) were measured 3.652 and 0.974, respectively. The identified butterflies in the campus are from families Nymphalidae (20 species), Pieridae (8 species), Hesperiidae (5 species), Lycanidae (4 species) and Paplionidae (3 species). The findings showed a marked diversified pattern of butterfly species. This may be attributed to the more diverse habitats in Lucknow region.